2017
DOI: 10.1016/j.humpath.2016.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the prognostic role of the "Helsinki Score” in 225 cases of adrenocortical carcinoma

Abstract: Adrenocortical carcinoma patient prognosis is extremely variable and poorly predictable. The newly introduced Helsinki Score is the first so far proposed diagnostic and prognostic system based on the combined evaluation of morphological (mitoses and necrosis) and immunohistochemical (Ki-67) parameters. The aim of the study was to validate the prognostic role of the Helsinki Score for adrenocortical carcinoma characterization. Thus, 225 adrenocortical carcinomas were reclassified using the Weiss Score and the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 22 publications
1
71
0
2
Order By: Relevance
“…In humans, the prognosis of patients with an ACC does not only differ from that of patients with an ACA, but the prognosis also varies greatly within the group of patients with an ACC . In human ACCs, histopathological criteria that are associated with a poor prognosis include high mitotic rate, high Ki67 proliferation index (PI), and high Helsinki score …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In humans, the prognosis of patients with an ACC does not only differ from that of patients with an ACA, but the prognosis also varies greatly within the group of patients with an ACC . In human ACCs, histopathological criteria that are associated with a poor prognosis include high mitotic rate, high Ki67 proliferation index (PI), and high Helsinki score …”
Section: Introductionmentioning
confidence: 99%
“…The differentiation between an adrenocortical adenoma (ACA) and adrenocortical carcinoma (ACC) is usually based on histopathology. Although several studies have been conducted on the histopathological analysis of human ACTs, [2][3][4][5][6][7][8][9] the literature on canine ACTs is less extensive. The most recent study on histopathology of canine ACTs was published in 2004, in which the authors compared a number of histopathological criteria between ACAs and ACCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This system was shown to be able to predict the metastatic potential of ACC with very high sensitivity and specificity (Pennanen et al 2015). Another very recent study extended and confirmed the prognostic validity of the Helsinki score on a larger series of ACC cases (Duregon et al 2017).…”
Section: Histopathological Evaluation Of Malignancy In Act: Around Anmentioning
confidence: 82%
“…A recent large multicentric ENS@T study has shown that the KI67 LI is a very reliable parameter to predict disease recurrence (disease-free survival, DFS) and overall survival (OS) in ACC patients after complete tumor resection . Furthermore, Ki67 LI integration with morphological parameters in the newly introduced Helsinki score makes it to outperform the Weiss system as a prognostic indicator in ACC (see above) (Pennanen et al 2015, Duregon et al 2017. However, a limitation of the Ki67 LI consists in difficulties in its standardization and reproducibility when applied to many tumor types, including ACC (Papathomas et al 2016).…”
Section: Immunohistochemical Markers Improve Prognostic Assessment Inmentioning
confidence: 99%